2011
DOI: 10.4012/dmj.2010-135
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of a PMMA resin for fixed interim prostheses with nanodiamonds

Abstract: The aim of this study was to investigate the possible reinforcement of Nanodiamonds (ND) in a PMMA resin for fixed interim restorations. The fracture toughness (KIc), impact strength and the dynamic thermomechanical properties (Tg, E´, E´´, tan) of a series of PMMA-ND nanocomposites with different amounts of ND were evaluated. The fracture toughness increased as the ND percentage increased up to 0.38% wt but a greater amount of ND induced a decrease in KIc. Impact strength and Young's modulus were also increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 52 publications
2
48
0
1
Order By: Relevance
“…101,102 NDs significantly increased the impact strength of PMMA, and also improvement in fracture toughness was found, but only at the lowest concentration of NDs. 103 Moreover, heat-treated NDs increased the scratch resistance of PMMA. 104 Some drawbacks were attributed mainly to agglomeration of the NPs, which could act as points of stress concentration.…”
mentioning
confidence: 99%
“…101,102 NDs significantly increased the impact strength of PMMA, and also improvement in fracture toughness was found, but only at the lowest concentration of NDs. 103 Moreover, heat-treated NDs increased the scratch resistance of PMMA. 104 Some drawbacks were attributed mainly to agglomeration of the NPs, which could act as points of stress concentration.…”
mentioning
confidence: 99%
“…45,46 The aim of this review is to provide an overview of the research that has been conducted on NDs as dental biomaterials. In addition, the potential of NDs for dental applications and toxicological aspects have been discussed.…”
Section: Accepted Version Science Of Advanced Materialsmentioning
confidence: 99%
“…Recent research by Protopapaet al studied the mechanical properties of polymethylmethacrylate (PMMA) denture polymer reinforced by addition of 20nm nanoclusters of NDs. 46 They observed that the PMMA resin containing 0.83 wt% NDs, at 2084 MPa, had a much higher modulus of elasticity (Young's modulus) when compared to unmodified resin which had a modulus of 1184 MPa in addition to improved fracture resistance and impact strength. 61 However, properties such as bond strength of nanodiamond-composites to tooth structure and microleakage have not been studied yet.…”
Section: Accepted Version Science Of Advanced Materialsmentioning
confidence: 99%
“…Diferentes métodos para melhorar as propriedades dos materiais para PPF provisórias tem sido avaliados (6)(7)(8). Resultados positivos têm sido encontrados utilizando metal e fibras como reforço (7,(9)(10)(11)(12)(13).…”
Section: Conclusãounclassified